6 - L’espace public au ras du sol en postcolonie : travail de l’imagination et interpellation du politique au Cameroun - Abé, Claude (Africa Development, 2021)
This article focuses on public space as it can be seen from the grassroots level in Africa. The experience of Cameroon under the single party shows how ‘the grassroots’ capitalizes on social imagination and takes an indi- rect route to political interpellation. The hypothesis upheld here is that observing social practices in single-party Cameroon cannot be reduced to the mobilization of the category of subjection alone without being seriously impoverished, since the social actors evolving on the side- lines do not lack initiative. And these forms of initiative, which are often overlooked, are our focus in this study. The focus is particularly on those that contribute to the construction of a public speech culminating in the critical mediatization of the established order. By public speech, we mean any practice, discursive or not, that has a public function. To study such practices in terms of critic civility, we will draw inspiration from the work of Bakhtine and the everyday sociology of de Certeau. The research focus is on the discovery of the rationale behind the daily collective practices of the people of Cameroon. Thus oriented, the aim of this article is to uncover the political inter- pellation at work in the ‘ways of speaking’ and the ‘ways of doing’ of the grassroots people. It focuses on various daily operations that are not overtly challenging, but that still express the idea that the people have of the management of matters of public interest. Some use a ‘common stock of available knowledge’, some use imagination and others appropriation after transformation. This article is divided into two parts. The first shows how ordinary people take advantage of vampire stories and rumours to describe the political regime in place and the social order it exudes. The second concerns the practices used by the grassroots people to fool the authorities by doubling what is offered to it in terms of consumption of another meaning that is challenging to the established order.